2018
DOI: 10.2139/ssrn.3140345
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Responses to Disability Benefit Cuts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, research has shown that inducing work take-up among long-term beneficiaries can be difficult and results regarding the employment capabilities of this group are mixed (e.g. Kornfeld and Rupp 2000, Adam et al 2010, Borghans et al 2014, Bütler et al 2015, Moore 2015, Garcia Mandico et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown that inducing work take-up among long-term beneficiaries can be difficult and results regarding the employment capabilities of this group are mixed (e.g. Kornfeld and Rupp 2000, Adam et al 2010, Borghans et al 2014, Bütler et al 2015, Moore 2015, Garcia Mandico et al 2018.…”
Section: Introductionmentioning
confidence: 99%